KESEJAHTERAAN PENDUDUK ANTAR NEGARA DIUKUR MENGGUNAKAN GDP PERKAPITA DAN GDP-PPP PERKAPITA - Chandra Utama (Center for Economic Studies Universitas Katolik Parahyangan, 2013)
Generally, percapita GDP in US Dollar is used to measure the everage welfare in a country. Forhermore, the level of welfare between countries can be compered using percapita GDP. However, the price differences among countries make the comparison is not accurate. GDP purchasing power parity (GDP-PPP) is created inspired on theory of purchasing power parity (PPP). The average income percapita between counties that same as percapita consumption of goods and services is more accurately measured using percapita GDP-PPP. The price of goods and services in percapita GDP-PPP are assessed using international prices.This study used data from 183 countries in period 2005-2010. The study found that the average income among countries in percapita GDP and percapita GDP-PPP are not different. The study also discovered the large inqualities of walfare between countries in the world. Nevertheless, the inequalities are relatively more meaninfull when the percapita GDP is used rather than percapita GDP-PPP is used. It is found, if using percapita GDP, the average income per capita of low-income economies, middle-income economies, and some high-income economies are measured too low, on the other hand income percapita of some high-income economies are measured too high. As consequency, the percapita GDP-PPP for low-income economies are more than three times larger than percapita GDP. How many times the percapita GDP-PPP large than the percapita GDP are reduce when the income percapita of the countries go up. It also found, there are many countries that move to higher group of income when using percapita GDP-PPP. Key words: GDP, Purchasing power parity, welfare